Draft Annual Plan 1986-87 Volume XII Social Welfare, Labour Employment and Information Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
During the 7th Plan period stress has been given to improve the living conditions of the Scheduled Castes and other down trodden sections of the society. For this purpose, during the 7th plan period an outlay of Rs 594.00 lacs has been approved as against Rs 329.00 lacs in the 6th plan period. Similarly at the Social welfare front an outlay of Rs 260.0 lacs has been approved in the 7th plan as against the total outlay of Rs 250.00 lacs in the 6th plan. Under Nutrition an outlay of Rs755.00 lacs has been approved for the 7th plan against Rs 120.00 lacs during the 6th plan period. It is quite clear from this that an increase of 231% has been made for the 7th Plan.
Jammu and Kashmir Government, Planning and Development Department